2018
DOI: 10.1088/2053-1591/aaf251
|View full text |Cite
|
Sign up to set email alerts
|

Study on the wear resistance of laser cladding iron-base alloy by heat treatment

Abstract: The wear resistance of laser cladding iron-based alloy experiment has been carried out by the friction and wear experiment and a number of tests. Heat treatment of weld was further studied through microstructure observation, hardness test, the quality of wear and wear appearance. The results show that the crystalline grains of the heat treatment scheme are homogeneous and smaller. Meanwhile, the wear quality and friction coefficient are reduced and the wear morphology is improved. The wear situation of the non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Guo et al studied the mechanical properties of iron base laser cladding coatings under the influence of heat treatment. With the result that the optimal wear resistance of the coating can be obtained after 850 • C heat treatment [22]. The above research shows that heat treatment has a positive effect on the mechanical properties of the coating.…”
Section: Introductionmentioning
confidence: 62%
“…Guo et al studied the mechanical properties of iron base laser cladding coatings under the influence of heat treatment. With the result that the optimal wear resistance of the coating can be obtained after 850 • C heat treatment [22]. The above research shows that heat treatment has a positive effect on the mechanical properties of the coating.…”
Section: Introductionmentioning
confidence: 62%
“…The friction coefficients of the coating after heat treatment were decreased, obviously. Guo et al [14] investigated the friction and wear properties of laser cladding iron-base alloy by heat treatment. The results showed the crystalline grains of the coating are smaller after heat treatment for austenite and lath martensite grains, which are helpful in improving the hardness.…”
Section: Introductionmentioning
confidence: 99%
“…The friction coefficient of the coating decreased significantly after thermal treatment. In the study by Guo et al [15], the friction and wear properties of the iron-based alloy cladding layer after thermal treatment were investigated. The experiment showed that the grain size of the thermal treatment scheme is small, and the austenite and lath martensite grains are obvious, which is beneficial to improve the hardness.…”
Section: Introductionmentioning
confidence: 99%